Profile of Mean Platelet Volume (MPV) in Patients with Nasopharyngeal Carcinoma before Undergoing Therapy in Sanglah General Hospital Denpasar - I Gde Ardika Nuaba (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal carcinoma (NPC) is a head and neck malignancy that is endemic in Southern China and Southeast Asia, including Indonesia. Currently, the TNM classification based on anatomical information is the most commonly used staging system. However, large variations were reported in clinical outcomes from one patient to another, even though they were at the same stage and had the same management strategy. MPV is an indicator of increased platelet activation and can easily be detected from peripheral blood through complete blood count analysis. MPV can be used as a marker of angiogenesis in patients with malignancy because of the role of platelets as angiogenic, metastatic and proteolytic in the inflammatory process of malignancy. Objective: To investigate the Mean Platelet Volume (MPV) profile in Nasopharyngeal Carcinoma patients before undergoing therapy at Sanglah General Hospital, Denpasar. Methods: This study was a cross-sectional descriptive study with 77 samples from April to June 2020 by performing a complete blood count in patients who had recently been diagnosed with nasopharyngeal carcinoma and had never undergone other treatment related to malignancy such as radiotherapy and chemotherapy. Results: The MPV value increased the most in male group compared to the female group (87.5% : 71.4%). MPV value is also have increased the most in the age group >50 years compared to other age groups (83.6%). Clinical stage IV is known to have increased the MPV value the most compared to other clinical stage groups (100%). There was an increase in the MPV value most in the histopathological type group of NKSCC compared to the other histopathological type groups (83.7%). Conclusion: The MPV value most increased in the male group, the age group >50 years, clinical stage IV group, and the histopathological type group of NKSCC.